Tales from Du Bois : the queer intimacy of cross-caste romance - Williams, Erika Renée, 1973- (State University of New York Press, 2022)
"Offers a new framework for understanding Du Bois's poetics and politics, including the concept of double consciousness, by tracing the trope of the cross-caste romance across his fiction"-- Provided by publisher.
Keywords: Du Bois, W. E. B. -- (William Edward Burghardt), -- 1868-1963 -- Criticism and interpretation.; Du Bois, W. E. B. -- (William Edward Burghardt), -- 1868-1963; Interracial couples in literature.; Caste in literature.; Couples mixtes dans la littérature.; Castes dans la littérature.; LITERARY CRITICISM / American / African-American.; Caste in literature; Interracial couples in literature; Criticism, interpretation, etc.